Adaptive switching detection algorithm for iterative-MIMO systems to enable power savings - Tadza, N.; Laurenson, D.; Thompson, J. S. (Radio science, 2014)
This paper attempts to tackle one of the challenges faced in soft input soft output Multiple Input Multiple Output (MIMO) detection systems, which is to achieve optimal error rate performance with minimal power consumption. This is realized by proposing a new algorithm design that comprises multiple thresholds within the detector that, in real time, specify the receiver behavior according to the current channel in both slow and fast fading conditions, giving it adaptivity. This adaptivity enables energy savings within the system since the receiver chooses whether to accept or to reject the transmission, according to the success rate of detecting thresholds. The thresholds are calculated using the mutual information of the instantaneous channel conditions between the transmitting and receiving antennas of iterative‐MIMO systems. In addition, the power saving technique, Dynamic Voltage and Frequency Scaling, helps to reduce the circuit power demands of the adaptive algorithm. This adaptivity has the potential to save up to 30% of the total energy when it is implemented on Xilinx®Virtex‐5 simulation hardware. Results indicate the benefits of having this “intelligence” in the adaptive algorithm due to the promising performance‐complexity tradeoff parameters in both software and hardware codesign simulation. Key Points Adaptivity achieves optimal error rate performance with minimal powerReceiver adapts to conditions according to the mutual information thresholdsDVFS technique reduces the circuit power demands of the adaptive algorithm